Venesection reflective essay - Hochman, David George (My University, 2018)
The complexity of this undertaking will become evident, if it hasn‟t throughout the novel, as it had to me soon as I began to write the work. I had described to my supervisor that this novel was a “slog” to write. I did not mean this, however, in the conventional sense, that it was hard work—which it was, like any novel. What I meant, rather, was that the situations and background I wished to portray or at least have as a backdrop (in terms of influence upon the characters) were madness and chaos. That to read a sensible novel about such madness and chaos would be to the reader not the most sensible thing. A work on suffering ought not be a pleasant undertaking. I realized, that the only solution was to also make the novel „mad and chaotic‟, to make the reader as confused as the character that had found herself in a concentration camp at a young age and forced to undergo horrors, many of which she has been reluctant to discuss until now. We, as the readers, should feel that much of what she says is as chaotic in her remembrances as her experiences. No one could make sense of it, not the survivors, certainly. Just as likely, when the madness died down as abruptly as it started and latterly been uncovered, probably not even by some of the perpetrators, who had come from ordinary backgrounds and professions to slaughter people at will, only to return to conventional professions as if nothing had occurred. It is important to note that only approximately 10% of the concentration camp personnel were ever prosecuted. A full 90% returned to life as if nothing had occurred; countless with no remorse (like Eichmann, Stangl, Höss, etc.). Many moved up in post-war East and West Germany to highest ranks of society. The main character, Klara, a Holocaust survivor, and her son, Anton, reunite after decades apart; Klara also gets to meet her granddaughter, Lucie, for the first time. Once they reunite, they and Anton‟s girlfriend and the novel‟s other principle character, Annie, a police officer, are forced to live and relive events that remind Klara of her experiences from the war. To the reader, the scope may not seem similar, but it was important to portray pain as unilateral, his and Annie‟s and Lucie‟s no less than Klara‟s, since all the characters have suffered at the hands of an abusive entity. Additionally, such triggers are entirely individual. It was important to show that the pain was to each the same and that each suffered the damages such pain inflicts. The novel, after all, is about suffering, universal and individual, that some people inflict upon one another. It is also, as sub-themes imply, about whether evil resides in every heart (something the novel fundamentally disclaims as a universally accepted cliché, an easy excuse for those that have committed such atrocities or wrongs) and proves rather simply, by historical examples of those that could have given in to evil but remained brave and often gave up their lives. The main premise is whether someone who went through such atrocities would be able to prevent them from happening again. Once again, the novel has answers: it depends on the character of the people involved. But those characters can be creative, or seek help, if they are unable to be courageous themselves. The backbone of the novel is the Klara‟s friendship with Annie and the repercussions for all characters involved. The setting is predominantly the US, Florida specifically, where Klara has retired and Anton and his family join her and where Annie lives. Klara makes comparisons between Nazi Germany and the US today because those are the two societies she has come to know the longest and best. And she is aghast at how futile are laws in a democracy the world looks up, no less so than the laws of Nazi Germany had been. On a far smaller scale, the setting is South Africa, only inasmuch as Klara describes who Anton‟s father is and where Anton was born, but she remembers little of it and little of his father, since her time there and with him was brief and severely limited. She makes no commentary on South Africa since it is a country she knows little. It is also not by any means the scope of this novel; neither is her relationship with Anton‟s father, or Anton with his father. This is a story of two central characters, Klara and Annie, and whether history‟s wrongs may be prevented. South Africa merely serves as a backdrop to suggest that Klara may have done things in the post-war years of which she isn‟t proud of and which she hardly understands and that may be a direct result of her war experiences; as such, it might be evident to the reader that she has colored that part of her past. The novel attempts to deal with topics that hardly make sense: individual and universal suffering; victims‟ shame, perpetrators‟ lack of remorse; the ability of some victims to recover but not others. The incongruities are endless; there are no easy answers to the questions raised by the events lived and described by the characters. Let us begin by trying to ascertain the incongruities and the difficulty of trying to portray the sociopaths (interchangeable with psychopaths and those with Antisocial Personality Disorder (APD) for the purpose of this essay). And that already begins to be an interesting undertaking. “People with severe Antisocial Personality Disorder (APD) don‟t experience normal guilt when they break rules or hurt people, so they lie, cheat, con, steal, and behave aggressively without qualms” (Kaufman, 2010). Kaufman stresses that psychopaths (people with APD) are not psychotic—she says this is an important distinction, where “psychosis is a loss of contact with reality…” (2010). Therefore, and importantly, “to get away with multiple dangerous crimes, planning and forethought are necessary. The deterioration of organized thought and behavior associated with psychosis makes successful planning nearly impossible” (2010). The antagonist, Carolien, knows precisely what she is doing. She plans accordingly, with great specificity and duplicity. She is violent, in a controlled manner, and she is remorseless. She knows precisely, as such individuals often do, how to manipulate people and the system in her favor, very much as the Nazis had done in Klara‟s time. “The truth is that just as religious beliefs, sexual orientation, and ethnicity can be inconspicuous, psychological disorders are usually invisible to the casual and sometimes even the careful observer” (2010). This is important because during writing this novel I found that, as a writer, persuading a female readership about the evil of a female psychopath was not without challenges (it was far more difficult to elicit sympathy for a husband beaten by his wife than a wife beaten by her husband—society turns a blind eye to the one scenario while rightfully condemning the other when, in reality, violence should be abhorrent no matter the sex of the perpetrator or victim). In this case, Carolien is described as attractive and more than willing to use sex to achieve her goals. Outwardly, she is adept at deception. She easily fools people at the crisis center, using a worker there, Suzette, to her benefit; as well as educators and men in the town she can use to her plan, specifically her older, wealthy new love, Chuck. Kantor writes, “statistically speaking, few individuals look or are markedly abnormal” (2006). “There are other seemingly radical incongruities, for instance, that between the face, the features of a person, and his (or her) real character” (Adler, 1918). Once again, it was not easy for a readership, I found, to equate violence with an attractive feminine character. And that made the antagonist to this writer particularly appealing as a character: it goes very much against the expectation of women and mothers to the average reader. Especially if one goal might be this: “Every mother looks into her child‟s eyes for an image of her own goodness. But when she is expecting that very soul will be saved by her child, we can be sure that violence is in the offing” (Kaplan, 1992). As I was to find out only after beginning the project, not only are psychopaths hard to catch in real life (they are simply too intelligent—in this particular manner—and too calculating, cunning and free to act without empathy) but also, they don‟t stand out physically or are obvious mentally, inasmuch as we would like. They are not necessarily unattractive, or mentally deficient or have physical attributes to give them away: on the contrary, they are often pillars of society, smart, attractive, persuasive. Or, at the very least, they blend in, inconspicuous. They are people like the cook, Kurt Franz (or the chicken farmer, in the case of Himmler), who becomes a vicious killer in the concentration camp only to go back to being a cook. To a person with a sense of morality, this is a dilemma that is hard to grasp. In literature, it is even more difficult to capture and portray, because the perpetrators, although capable of monstrous acts, are rarely, to the naked eye, the physical monsters we would like them to be (true-life holiday photos of female concentration camp guards singing and eating would never give away their daytime jobs). It frightens and confuses that the person we buy bread from at the bakery may be entirely capable of gassing us the next day. The notion is so absurd that for a person with a normal sense of morality, it is unfathomable; which is precisely why Carolien makes for an intriguing character; and why she grates the pre-conceived notions of womanhood and motherhood. Any caring and loving mother should find Carolien a most uncomfortable character to read. Female readers have so far commented that in Carolien they see their own shortcomings, when they don‟t exist in reality. This is something male readers have not voiced: a male reader does not automatically see themselves in a psychopath in a novel. And yet mothers, inexplicably, have found Carolien a disconcerting character and presence. Perhaps for this reason, as readers, we need to see such individuals as conventionally evil as possible in literature, in films (large, unattractive or at least masculine perpetrators beating people, killing people, performing heinous acts). The reality, that they are not recognizable by the naked eye or through conversation; or that most readers do not equate them with people dainty, feminine or attractive; was interesting to this writer (and, of course, to the likes of Hannah Arendt), at the very least. As Kantor reminds us, “alas, only in fiction, not in real life, do most psychopaths come to unhappy ends” (2006). In reality, they mostly lead remorseless, productive, often very successful lives, rewarded for their deceit and villainy; in full contradiction of how things ought to be in a just world, the victims, not the perpetrators, carry the burden of pain, shame, and often even guilt for the rest of their lives. The perpetrators carry no remorse, because of “…the psychopath‟s tendency to view sources outside of himself or herself as the cause of his or her problems…” (Doren, 1996). Because the psychopaths are so very good at blending in, they are often the most „normal‟ of individuals. To the point, as Hannah Arendt reminds us, of banality (Arendt, 2006). Arendt goes further. According to her recollection of Nazis: “…the murderers were not sadists or killers by nature; on the contrary, a systematic effort was made to weed out all those who derived physical pleasure from what they did” (2006). From a literary point of view, we are accustomed to evil being evil and good being good and both evident; where we can easily recognize the protagonist and antagonist and the antagonist displays clearly mental and physical deficiencies or attributes which make us exclaim while we read or watch a movie, “There he or she is! There they are, watch out, behind you!” To the reader or the viewer, this is quite often glaringly evident, if not immediately to the characters on paper or the screen. This lack of certainty, this ambiguity, is much more interesting to overcome as a writer, if one wishes to portray a psychopath as they mostly exist, in all their ordinariness, or indeed glory. Unless one gives the antagonist(s) clearly defined attributes or actions (and often not even then), the reader has the same problem that confronted Hannah Arendt with, and in the writing of my novel, the utterly ordinary appearance of people who commit utterly heinous acts. A woman, a mother, who abuses her husband or child, something just as common as any other abuse but hardly acknowledged or confronted at present, is far more difficult to grasp vis-à-vis our sacrosanct acceptance of motherhood; and therefore makes readers uncomfortable, especially female ones. As if that were not difficult enough a challenge, another emerged: what I had found as utterly heinous as acts that occurred to my characters, some readers found blasé or melodramatic or both. Precisely the mocking indifference that Wiesel‟s Moishe the Beadle captures vividly (as described in greater detail later in this essay). That is not to say that Arendt was making light of the crimes, either; rather, I believe, it was her inability (and the readers‟ inability), to their credit, to come to terms with the barbaric acts of individuals. Upon its publication, because of the writer‟s views, Amos Elon states in the introduction about Arendt, “a kind of excommunication seemed to have been imposed on the author by the Jewish establishment of America” (Arendt, 2006). I thought, as I wrote this novel, that I began to understand this somewhat (if it can be understood). I grappled with similar challenges as Arendt. She could not marry the image one has of a psychopath capable of delivering hundreds of thousands if not millions of people to their deaths with the utterly ordinary looking figure of Eichmann sitting in front of her on trial, sneezing from a cold. No more than a reader of my novel may understand a mother abusing her own daughter. As I read historical works further and deeper, even that incongruity became evident: horror as depicted to some may not be horror construed to others; some may also not wish or be capable of believing or understanding the horror if they had not experienced it themselves (any more than someone who has not survived cancer can fully understand what it is like to have cancer). Thus, in my view, an explanation for some sceptics, including some academics, to revise figures regarding those that perished from certain camps, as if somehow lessening the number murdered made it less horrible. We tend to think of the concentration camps as an organized killing machine. In many ways it was. But for those that were imprisoned there, it was also teeming with chaos. People came and disappeared. It was difficult to keep track of anything, time, days, years, in full comprehension. Rumors abounded. The black market thrived. One‟s previous profession, especially intellectual, mattered not in the least. The laborer or electrician might have much better chance of survival than a professor or an artist. “Prisoners survived by chance, they died by chance, and they knew it. In one instance, a group of women were rounded up at random and locked in the gas chamber. All night they stood jammed against each other waiting; at dawn they were released because the SS had run out of gas, and by the time the next supply arrived, it was someone else‟s turn. And always, around the corner, around this one, there might be an SS man drunk and killing for the fun of it” (Des Pres, 1977). Vrba adds: “Their hands were never far from their revolvers and even without provocation they would draw them and shoot a prisoner in the face at close range” (1964). And what about the women‟s role in the carnage of the war? And the camps, specifically? “As we have seen, at least half a million women witnessed and contributed to the operations and the terror of a genocidal war in the eastern territories” (Lower, 2014). And that is only in the eastern territories. How many in the entire war? A million? And what happened to them? “Most German women who participated in the Holocaust quietly resumed normal lives” (Lower, 2014). I began to understand that if it was difficult enough to find Eichmann a monster even for someone like Hannah Arendt, then it would be that much more difficult to portray the female antagonist in the mind of the reader, especially a female reader, as the evil antagonist the novel would require, masked in attractiveness, allure and intelligence. That the sanctity of womanhood and motherhood would further weaken the case for a psychopath. Lower, herself, an expert on the subject of female perpetrators during the war, had the same difficulty: “When pressed by the interrogator as to how she, a mother, could murder these children, (she) referred to the anti-Semitism of the regime and her own desire to prove herself to the men. Her misdeeds were not those of a social renegade. To me, she looked like the embodiment of the Nazi regime” (2014). I had several options. This was, after all, not a memoir in the vein of Primo Levi‟s Survival in Auschwitz: If This is a man, or of Elie Wiesel‟s Night. Even those works, I thought, found it difficult enough to capture the horror, for horror inflicted by humans upon humans becomes a multi-faceted, complicated chapter of humanity, inflicted by human beings indiscernible to the naked eye and rather different once removed from their roles as torturers and murderers. Arendt informs us: “Despite all the efforts of the prosecution, everybody could see this man (Eichmann) was not a „monster‟, but it was difficult not to suspect he was a clown” (2006). What Arendt fails to consider, in my opinion, is that perhaps Eichmann, one of the masterminds of the Wannsee Conference, and thereafter the immense logistics required to bring about its goal, is playing the rest of the world for a clown, this might be his ultimate performance to save his life, pretending to be a pathetic buffoon. A sort of, do you really think someone who looks and talks like me could be capable of such horrors? How difficult would it be for a truly intelligent psychopath—and we have no reason to believe that a man who can mastermind the logistics of millions of people to their deaths in a most complicated system was anything but extremely intelligent—to pretend he is but a buffoon in front of a world audience, mumbling inanities while hunched over and sneezing from a cold? Photographs of him in Nazi uniform depict an entirely different individual from the incarcerated self. If we accept that anyone who is partly responsible for the deaths of hundreds of thousands if not millions of human beings is a psychopath; and we know that a psychopath is not psychotic but fully aware of his or her actions, incredibly intelligent to the point of being able to plan to the tiniest detail in advance to attain goals; then the only logical conclusion is that evil remains evil, not banal, that perpetrators will do anything—including acting the forgetful clowns—to save their skins. They are ultimately the consummate survivors, as the vast majority of Nazi killers had proven over and over in escaping the noose. I sympathize with Arendt that the more I learned of true evil, as it were, the more difficult it was to categorize, as a writer is wont to do for his sake as much as readers‟ sake; to simplify, to place characters into neat boxes, those of protagonists and antagonists. I sympathize with Arendt‟s need to call a real-life antagonist like Eichmann a clown—when to those who lost family members because of him, he is quite evidently a monster. And perhaps therein lies the quandary that I was trying to attain in the writing of this novel. Unlike Arendt, I did not see these perpetrators as clowns, or pathetic buffoons, but it became apparent that to the readers, there was a chance they would nevertheless remain so. It was clear in the workshops, as my work was read, that some readers had difficulty accepting or understanding horror or tragedy any more than Arendt could accept the fact that Eichmann and his ilk were monsters. I began to realize that if I were not to write a memoir and I did not want to make a mockery of human tragedy or make a lighter version of it as the film Life is Beautiful mostly managed to do (though not to everyone‟s satisfaction or acceptance); and if I did not wish to make the villain a traditional villain (a slasher of bodies, for example); then the only solution was to to paint a tapestry, as it were, one of some ambiguity and chaos. For the deeper I delved into the constitution of a psychopath, the deeper I delved into events that entangled one of the main characters, Klara; the more confounding the exercise. I could not categorize or depict evil as a banality; the victims‟ dignity depended on it. I did, however, wish to obfuscate the events, if not the actions. I wanted to describe events in the same way as the survivors, and by the Nazi perpetrators. By the former, because it was impossible to make sense of events or because they often refused to talk about experiences; by the latter, because they did not see themselves as perpetrators. Rather, they saw themselves as obediently fulfilling duties as required by the law of the land, another ambiguity. If the perpetrators truly saw themselves as innocents carrying out the rule of law, why the ruse? Why attempts to hide the truth or events (as Sereny informs us, Treblinka was razed and over the remains a farmhouse built; a Ukrainian farmer was to tell visitors he had been farming there for years)? Just in case the war was lost? And if that possibility even existed, then why eliminate the „undesirables‟? For surely, in the event of defeat, the odds of an Aryan Germany surviving were inconceivable, if Germany survived at all. After all, it was unthinkable to Hitler that any semblance of Germany or Germans could survive without him. And yet, that is what they did, try to hide the facts. “Furthermore, all correspondence referring to the matter was subject to rigid „language rule‟, and, except in the reports from the Einsatzgruppen, it is rare to find documents in which such bold words as „extermination‟, „liquidation‟, or „killing‟ occur. The prescribed code names for killing were „final solution‟, „evacuation‟ and „special treatment; deportation—unless it involved Jews directed to Theresienstadt, the „old peoples‟ ghetto‟ for privileged Jews, in which case it was called „change of residence‟—received the names of „resettlement‟, and „labor in the East‟, the point of these latter names being that Jews were indeed often temporarily resettled in ghettos and that a certain percentage of them were temporarily used for labor” (Arendt, 2006). The benign names masked not only the horrors of the camps, but horror of everyday life, now accepted as completely normal. “Jews became the slaves and playthings of their German overseers. Killing Jews became a source of amusement, like hunting rabbits. As one Jewish survivor recalled: „(The Germans) were all drunk, lying around in their seats in the carriage hugging and shouting, their peals of laughter echoing in the distance. The carriages galloped between rows of (Jewish) marchers and the shouting grew louder. The wild Germans mocked the Jews, laughed at them, and struck those nearby with their whips. One of the drunken officers aimed his hunting rifle and started shooting at the Jews to the raucous pleasure of his staff. The bullets struck some marchers who collapsed in pools of blood‟” (Lower, 2014). And such scenes in the open, in the countryside, let alone in the concentration camps. I chose this topic because it was close to my heart. My father had survived a concentration camp, captured as a seventeen-year-old member of the resistance, and he remembered such scenes vividly. Yet, one had to push him for details, they were never volunteered; and even then, he was reticent. I knew that he had recurring nightmares, almost daily he said, seventy years later. Events were remembered, but events had been suppressed, too. Some memories would change and blur, some remained constant and detailed, some were suppressed if not wholly forgotten; but the notion of horror in the absolute, what it felt like, remained the same. And yet, it was almost impossible to describe, especially to those who had not lived it or experienced it. I remember specifically an intimate friend of his, Alexander Zemanek, interviewed by the Shoah Foundation on November 25, 1996, responding to my question what Buchenwald was like with an initial laugh. From memory, he said something along the lines: It was organized chaos, it was a blur, it was manslaughter, it was pain, it was dread, utter confusion. It was all that and it was none of that. It was something I can never fully describe to myself or anyone else. Indeed, if one reads accounts of Primo Levi, of Elie Wiesel, amongst others, as horrifying as they might be, they feel as if one is only reading the tip of the iceberg, as if it is impossible to truly capture all that had transpired, all that they had endured. I believe, writing this novel, that I at least a little understand why. Because it is impossible to make sense of it in any reasonable way. Because it is impossible to say, these were the perpetrators, here‟s how you can recognize them, here‟s why they had done what they had done, they knew that they had committed horrors and they were punished. The facts are that any of the aforementioned statement is precisely the opposite: who exactly were the perpetrators, why can we not physically recognize them, why had they done what they had done, why did they not recognize their acts as acts of horror and why were a vast majority unpunished? And if one cannot answer any of the points satisfactorily, then the only way I could see writing a novel that was in any way „realistic‟ or „truthful‟ was to write a chaotic and ambiguous one (but still one where justice is meted out, albeit too late for Klara). Chaotic in recollection, non-linear, in telling the stories, in terms of characters, of actions, of place and time. In the very same sense that a survivor might remember a detail or two, but not know which camp it was in, when it occurred, and at whose hands. Added to that is Arendt‟s assertion that the perpetrators were not monsters but clowns and the backdrop to the novel becomes murky indeed. A reader should therefore experience a similar sensation as anyone truly trying to understand evil: horror, confusion, buffoonery, incredulity, doubt, conviction, and so forth. I tried, in some small way, to parachute myself into one day in the life of a concentration camp and, like a movie director, say „cut‟ only to observe all the actors suddenly finding themselves in the moment of an atrocity, of cowering, hiding, of working, and asking themselves, perhaps, what in God‟s name am I, and have we been, doing here? It became apparent, in the workshops especially, that the more I tried to write a conventional story upon anything but an unconventional tale, the more it would be met with incredulity. Comments would abound such as, all the characters seem crazy. And it was then that I realized: well, perhaps they are all crazy to some extent. They certainly would be, wouldn‟t they, to the director walking around and asking such things as: why are you beating that man; why are you dressing these people in rags; why are you wearing wooden clogs, each a different size in the middle of winter; why are you gassing and burning them; why are you starving them; why is there only watery soup and scarce bread; why are you allowing them to treat you like this? Why, why, why? From the outside, would not the scene appear as one of utter madness, in all regards? The prisoners just as mad for putting up with the atrocities as the ones committing them? Would it not be akin to Primo Levi describing the scenes from Dante to a fellow prisoner, the youthful Alsatian, Jean, the Pikolo? “‟Think of your breed; for brutish ignorance. Your mettle was not made; you were made men, follow after knowledge and excellence.‟ As if I also was hearing it for the first time; like the blast of a trumpet, like the voice of God. For a moment I forget who I am and where I am” (Levi, 2008). And therein lies one of my many conundrums. What is madness? Are citing Dante and not rather keeping quiet--which in themselves could be causes for a beating if not a bullet to the head--not signs of madness? Or are they signs of beauty? And, if they are one or the other, if not both, how does one translate that into literature so that those uninitiated to horror can understand? Perhaps that is impossible to attain, but in some small way, in the telling of the story, in the changing point of view, in the changing of characters and tense and tales and reasons, in conjuring mayhem and chaos; it was at least a small way to try to capture the lunacy, which some see only as survival or following laws or no horror at all (if it hasn‟t happened to them). Where is the confluence of reason of those shooting in merriment from a carriage to those that are being shot? And how can one describe it with any relevancy, accuracy and meaning? I thought that, inevitably, the prose had to mirror the events, in its illogic, ambiguity, chaos and mayhem. There were times, therefore, that having the work read, I felt like Elie Wiesel‟s opening character, Moishe the Beadle, in Night. Moishe miraculously escapes being shot by the Germans in the first round-up to return to his hometown to warn the inhabitants of the Germans‟ atrocities. “But people not only refused to believe his tales, they refused to listen. Some even insinuated that he only wanted their pity, that he was imagining things. Others flatly said that he had gone mad. As for Moishe, he wept and pleaded: „Jews, listen to me! That's all I ask of you. No money. No pity. Just listen to me!‟ he kept shouting in synagogue, between the prayer at dusk and the evening prayer. Even I did not believe him. I often sat with him, after services, and listened to his tales, trying to understand his grief. But all I felt was pity. „They think I'm mad,‟ he whispered, and tears, like drops of wax, flowed from his eyes” (Wiesel, 2006). My father‟s friend, Alexander Zemanek, as mentioned, had acquiesced to telling parts of his experiences to the Shoah Foundation. He summarized years of suffering into two-and-a-half hours. I have not heard it (it is unavailable where I am); and I wonder, what could he have said in such a short amount of time regarding years of incarceration; and did he start with the same laugh with which he greeted my request to tell about the camps? Zemanek, after all, as many like him, hadn‟t even known he was Jewish when he was incarcerated for being Jewish. The madness and hell he entered, therefore, as only madness and hell perhaps can, began with an absurdity from the very beginning. Perhaps Milan Kundera said it best: “But why does God laugh at the sight of man thinking? Because man thinks and the truth escapes him. Because the more men think, the more one man's thought diverges from another's. And finally, because man is never what he thinks he is” (Kundera, 1988). Zemanek and other survivors suggested another quandary. Horowitz writes of Semprun‟s The Long Voyage: “Two days after liberation, the Holocaust has already become history, no longer present, no longer accessible. The narrator‟s personal experience, too, has become history, and he cannot communicate it to anyone who has not shared it. Moreover, as that experience recedes in time, he finds that he himself must struggle to connect with it” (Horowitz, 1997). Furthermore, “representations of what have been seen by witnesses are problematic not only because the witnesses have trouble finding the words to render the experience; they are problematic also because in the process of witnessing and testifying they exchange the event-as-memory for consciousness of the event, the event-as- knowledge. In the process of remembering the event for history, the witness elides aspects of the event that aren‟t available as testimony or as representation, aspects that for the reader or second-hand witness may well be overlooked” (Bernard- Donals, 2009). I had often asked my father why he had not told people his stories from the camps. To which he had replied that they would not believe it; and that the crazier the tales you tell, no matter how true, the crazier to a „normal‟ listener they appear, that in the end, it is you, the victim, that is not believed and shunned; and the perpetrators the ones who are accepted; that you only end up alone with your tales of woe. I was there when he took the call from the Shoah Foundation requesting an interview. Always calm, he grew irritable on the phone. He wanted to know how they defined being Jewish. According to the ludicrous Nuremberg Laws? he asked. Was it someone who went to the synagogue? Apparently, the interviewer did not answer satisfactorily and my father, who was the gentlest man I‟ve known, hung up the phone, refusing the interview. I looked into his sad, soft eyes and didn‟t ask why. But I think I already knew then and would only truly find out while trying to write this novel, that one could in no way authentically recount let alone explain the horrors he and others like him had endured at the hands of fellow human beings. One thing I knew from him was certain. The line that „evil resides in every heart and that anyone is capable of the same actions‟ was to him a falsehood; a convenient excuse of those who had committed atrocities. He had witnessed many people, he told me, who went to their deaths knowingly rather than betray or punish or kill their fellow man. Works of Wiesel, Levi and others attest to the same: cowardice or evil do not lurk in every heart. No matter what hardships or horrors or ultimately death the brave victims endured. But I am sorry that he had not given that interview, as much as I think I understand and respect the decision: two-and-a-half hours of testimony would have been better than none (at least from a family record standpoint). Let us now return to the difficulty of portraying a true-life psychopath in the realm of an Adolf Eichmann in literature. What we know of them: per Kaufman, they “function well enough in society…and successfully navigate the corporate world” (Kaufman, 2010). This doesn‟t need to be limited to the corporate world, of course. “Psychopaths are attracted by positions of power” (2010). They are also “persuasive…and intelligent, and their friends and partners may not realize that the psychopath sees them as completely expendable until they‟re no longer of use to them” (2010). Such is the character of Carolien, intelligent, persuasive. Her victims are expendable. Many researchers believe that psychopathy is incurable, simply because “(they) don‟t believe they have a problem, nor do they take responsibility for their actions” (2010). And yet, the common fallacy that they are emotionless is utterly untrue. They lack empathy but are by no means emotionless. They are more than capable of disappointment, anger and rage (if things don‟t go their way). They can, however, to a great extent, study and emulate emotions they are incapable of, even empathy. Love, however, in its truest deepest sense, eludes them. One need only think of perhaps the best-known psychopath, Adolf Hitler, and remember his genuine fondness if not outright love for his dogs, for Eva Braun, for his secretaries. He was, however, distinctly uncomfortable around children and as a rule, in most photographs and social settings, he stands to the side, alone, dating back to his days in the trenches in WWI. He had little or no time for camaraderie and bonhomie; and yet, despite that, he could persuade millions of people to lay down their lives for him and the lives of their partners and children and fight for him until only rubble remained. Even those that tried to assassinate him late in the war only did so to save their own skin. And yet, in literary terms, what sort of villain does a true non- violent psychopath make? As I was to learn the hard way, as Hannah Arendt was to learn to her dismay and that of her readers, not a very good one. One might even say a terribly ordinary one. One need only look at Himmler, Eichmann, Hitler, Goebbels, etc., to see a bunch of terribly ordinary and ordinary looking individuals; no intellectuals, if surely intelligent in whatever manner required to succeed in their quest; not particularly physical or strong. And yet, one mustn‟t be misled by the notion of buffoonery; they elicited terror in their ranks. They held millions of lives in their grip and control. That was precisely the problem I faced with my antagonist. Carolien is violent, she elicits terror in her victims. Yet she is a woman, a mother. It is just as easy to dismiss a mother as it is to dismiss a bumbling Eichmann. Eichmann in uniform, in his environment, wielding power, is not so easily dismissed. Still, my antagonist is not one of the central characters. Rather, her deeds are and so are their consequences. That way, I could elevate the story of the victims, the mother and her son and granddaughter and the son‟s girlfriend, the mother reliving through their pain what she had endured in the camps. Or at least that what she is willing to share with the reader. I tried to stick with my original theme: whether she would be able to „save‟ her son in modern day America any more than she could save her newborn children in a concentration camp. In other words, recounting victims‟ confessions, at the risk of being dismissed. After all, Wiesel lamented the difficulty in finding a French publisher (he had settled in France after the war) because potential publishers found it too gloomy. Levi‟s work, too, was at first rejected and only published by a smaller publisher. Nobody wanted to read the accounts, they were deemed too „depressing‟ and, perhaps, by the scale of horror, difficult to assimilate or relate to or understand by the uninitiated reader. There was additionally the automatic rejection of the material by the reader as „crazy‟, perhaps a natural reaction for which the reader should not be blamed. In my opinion, it is a genuine fear of the atrocities which some humans can unleash upon another, without rationale. There can be no justification for taking from a small village an innocent child and gassing and killing him or her. It is far easier to reject a psychopath for not being interesting or violent enough for literary merits, even to call them banal and clownish, than to admit that the chicken farmer living peacefully next door might the next day have you shot because of your religious or political beliefs or sexual inclination or ethnic origin, et al. That is something „normal‟ minds cannot potentially grasp or fathom. As Des Pres writes: “Merely because they are survivors, the men and women who passed through the camps are suspect in our eyes. But when we consider the specific nature of their identity—not only as survivors, but survivors of those places—suspicion deepens to shock and rejection. The concentration camp experience represents an evil so appalling that we, too, when we turn to face it, suffer psychic imbalance. We too flounder in nightmare, in a torment having nothing to do with us yet felt in some strange way to be very much a part of our deepest, most secret being” (1977). Thus, in my view, it is easy for the reader to see and depict such characters as crazy or banal, or both. I encountered other problems. One, the issue of why some survivors never recovered (the many) and why some thrived (the few) after liberation. I never found a simple or rational explanation and could therefore not incorporate it into the novel as I had wished. The survivors merely suggested that it was an ephemeral will to live, inexplicable, which some survivors possessed and many did not, turning them into musselmen. Vrba suggested that those that thought they survived through action as opposed to luck coped better after the war. In any event, it is a question without answer. Klara hasn‟t thrived, nor has she turned to musselman status— unlike her son, before Annie „saves‟ him. Klara has survived if not thrived, but her son‟s tragedy throws her right back into the hell of the camp that she had left behind. She feels the need to tell her story to Annie, who has lived her own atrocities, arguably no less painful. It is why the two women share a strong bond. In the novel, I try to tell the story in a somewhat chaotic haze. How a concentration camp survivor might view his or her experiences in later years (as my father and Zemanek tried to explain). Klara, Anton, Lucie and even Annie show signs of PTSD, originally known as concentration camp syndrome, as Gill informs us. Klara, Anton and Lucie, like many PTSD sufferers, have trouble sleeping, thinking, concentrating; they appear weak; they cry often; they are fearful. “Something about knowing that another human being has chosen to harm you or someone you care about overwhelms the psyche” (Kaufman, 2010). In Anton‟s case, that person is the one that, once his father passed away, he trusted the most, from where he initially expected no danger—his wife and mother of his child. He had done everything she demanded, he had taken her beatings, he had brought her to the USA; once there, she abandons him and takes his daughter. Klara, on the other hand, experiences „triggers‟. “People with PTSD have „triggers‟, which are unique to them. Triggers can be people, places, pictures, objects, or words that are somehow reminiscent of the trauma and therefore cause flashbacks, nightmares, overwhelming fear or anger, and fight-or- flight reactions” (2010). Klara, Annie and Anton know that there is something wrong with them, that they are severely traumatized. The irony is that, as experience from the war shows, the abuser, Carolien, is the only one who is utterly unaffected and believes herself to be utterly „normal‟. In conclusion, the novel was an interesting and fulfilling undertaking, in parts more difficult than envisioned. A topic as complicated as the Holocaust, as human abuse and suffering, could perhaps not have been any other way. For reasons mentioned, it was not as easy to create evil and good characters as anticipated. I had not counted on the „Moishe the Beadle‟ effect. The characters became rather more complicated. I had to overcome similar difficulties that Hannah Arendt struggled with when she accepted the assignment to cover the Eichmann trial in Israel for the New Yorker magazine. As Amos Elon wrote in the introduction to Eichmann in Jerusalem: A Report on the Banality of Evil: “Eichmann‟s mediocrity and insipid character struck Arendt on the first day in court… „he isn‟t even sinister,‟ she wrote… She ought to have known better. Hitler would not have cut a better figure under the circumstances. Out of power, most tyrants and serial murderers seem pathetic or ordinary, harmless, even pitiful…was she perhaps, at this early stage, a victim of…the Fallacy of Physiognomy?...(Eichmann) personified neither hatred nor madness nor an insatiable thirst for blood, but something far worse, the faceless nature of Nazi evil itself…” (Arendt, 2006). In my case, Carolien is manipulative, violent, deceitful. But she is not a clown. I wanted a genuine violent psychopath. I also wanted to emulate in a non-traditional way the horrors of the concentration camps—I didn‟t want to portray another sadistic Kommandant. I tried to make Klara‟s jailer, as it were, more ambiguous, more challenging, more mystifying and perhaps more frustrating as a character in that he was not so easily classifiable. Reading up on the survivors‟ tales, it was apparent that the camps were an organized mayhem. There were rules and regulations, but there was also a black market, theft; people meeting at night, love affairs, marriages, communication through wires. Everything was overlooked if prisoners were useful to a Kapo or a member of the SS. The scene was at once utterly terrifying, surreal, confusing (for the new arrivals especially) and absurd. Little was what it seemed. I tried to supplant the depictions in a similarly chaotic format. The storytelling is non-linear, the voices vary. I also gave fewer explanations about characters and what had occurred and who they were and how they related to one another. Again, this was on purpose. In the camps one was thrown together with complete strangers and had to quickly assimilate and figure out who was who, with minimal if any communication that was allowed and, even then, often in gibberish, since it was not uncommon to be placed with others from entirely different cultures, backgrounds and spoken languages. In this, I tried to stay true to the few recollections I had heard from my father, from Zemanek, and several other Holocaust survivors I had met and who were close family friends. They mostly spoke in general terms, vaguely, guardedly, mysteriously, reluctantly, and only very rarely did they speak about detailed instances. I tried to give the novel an authenticity. Similarly to how a survivor might reminisce about his or her experiences in the camps, none of which could have made much sense. The work is in memory to my father and Alexander Zemanek and Frantisek Kriegel and the others I have met and known who witnessed the basest of humanity‟s tendencies.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Creative Writing, 2018
Keywords: Creative writing; South African fiction (English); Fiction--Authorship